Renal impairment assessment on adults living nearby a landfill: Early kidney dysfunction biomarkers linked to the environmental exposure to heavy metals. (2021) - Cabral, Mathilde; Garçon, Guillaume; Touré, Aminata; Bah, Fatoumata; Dewaele, Dorothée; Bouhsina, Saâd; Cazier, Fabrice; Faye, Adama; Fall, Mamadou; Courcot, Dominique; Verdin, Anthony
Graphical abstract: Highlights: Health risk of the neighboring population of the Mbeubeuss landfill (Senegal). Assessment of the impact of Cd/Pb exposure through dysfunction renal biomarkers. Specific increases of a set of early dysfunction renal biomarkers in exposed subjects. Glomerular and tubular dysfunction in exposed subjects. Abstract: The aim of this study was to assess the integrity and kidney overall functional capacity of subjects exposed to landfill emissions. Urine and blood levels of Pb and Cd, and several of the newly biomarkers of nephrotoxicity (Kim Injury Molecule 1 (KIM-1), alpha-1 Microglobulin (α1 M), beta-2 Microglobulin (β2 M), Cystatin-C (Cyst C), Clusterin, alpha-glutathione S-transferase (GSTα), pi-glutathione S-transferase (GSTπ), Tissue Inhibitor of Metalloproteinase-1 (TIMP1), Calbindin, Neutrophil Gelatinase-Associated Lipocalin (NGAL), Osteopontin (OPN), (Retinol Binding Protein(RBP), Liver-type Fatty Acid-Binding Protein (FABP-1), Trefoil Factor 3 (TFF3), Collagen VI) were measured in order to assess glomerular and tubule damage in adults living near a landfill. Our results indicate glomerular dysfunction in exposed subjects, and supported evidence of necrosis of proximal and distal tubule epithelial cells as specific biomarkers began to appear in the urine. Positive correlation by Pearson test were obtained between : blood Pb and B-OPN, B-Cyst C, Calbindin, U-KIM-1, TIMP1, U-OPN, and U-Clusterin; and also, between urinary Cd and TIMP1, B-Clusterin, U-OPN, FABP-1, Albumin, and U-Clusterin. The relation between biomarkers of Cd/Pb exposure and early effect biomarkers in this study clearly predicts the future risk of severe kidney injury in subjects living close to the landfill.